FEASIBILITY TEST OF ENGLISH INSTRUCTIONAL MATERIALS FOR SECRETARIES THROUGH MOODLE - Didik Hariyadi Raharjo (JOALL (Journal of Applied Linguistics and Literature), 2020)
This research aimed to investigate the feasibility of EFS instructional material developed for ASTRI Budi Luhur students. The research was designed as qualitative and quantitative (mixed) approach. The method used in this study was the Delphi method, and the data were collected through questionnaires and interviews. Quantitative data were analyzed based on eligibility categories while qualitative data were analyzed to draw conclusions. The feasibility of the product of this research was examined by two experts in English for Specific Purposes (ESP) and instructional materials. The result showed that the instructional material was feasible with several improvements. Product feasibility test in this research was carried out three times. Each test was carried out after revising the draft of instructional materials based on input provided by the experts. In the last feasibility test, the experts gave a score of 3.7 for the syllabus and 3.7 for the developed instructional material, indicating that both the syllabus and EFS instructional material developed were very feasible to be applied in EFS learning in ASTRI Budi Luhur Jakarta.